2015
DOI: 10.1016/bs.pmbts.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Fulcrum

Abstract: Regulatory T cells (Tregs) are indispensable for immune homeostasis and the prevention of autoimmunity. In the context of infectious diseases, Tregs are multidimensional. Here, we describe how they may potentiate effector responses by assisting in recruitment of T cells into the infection site to resolve infection, facilitate accelerated antigen-specific memory responses, limit pathology, and contribute to disease resolution and healing, to the great benefit of the host. We also explore the villainous function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 154 publications
0
9
0
Order By: Relevance
“…In the setting of infection, the role of Tregs is complex and appears to be specific to a given pathogen. While some studies have shown that Tregs are detrimental to successful immune responses and in some cases can lead to establishment of chronic infection, others have shown that Tregs limit immunopathology (10, 1417). Studies of respiratory virus infections have yielded conflicting data about the role of Tregs in these different models.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of infection, the role of Tregs is complex and appears to be specific to a given pathogen. While some studies have shown that Tregs are detrimental to successful immune responses and in some cases can lead to establishment of chronic infection, others have shown that Tregs limit immunopathology (10, 1417). Studies of respiratory virus infections have yielded conflicting data about the role of Tregs in these different models.…”
Section: Introductionmentioning
confidence: 99%
“…Our results presented herein further support that an increased basal frequency of Tregs in the circulation correlates with protection both from early SARS-CoV viral replication, as well as from disease upon infection ( Figures 2 and 4 ). In the context of multiple viral infections, we and others have found that Tregs are critical to orchestrate proper anti-viral immune responses ( Lanteri et al, 2009 ; Lund et al, 2008 ; Pattacini et al, 2016 ; Ruckwardt et al, 2009 ; Soerens et al, 2016 ), while it has also been found that Tregs in the context of infections, including respiratory infections such as RSV and influenza, can assist in protecting the host from excessive immunopathology ( Belkaid and Tarbell, 2009 ; Brincks et al, 2013 ; Lee et al, 2010 ; Loebbermann et al, 2012 ; Richert-Spuhler and Lund, 2015 ; Smigiel et al, 2014 ). Thus, our results here further support the concept that balance between anti-viral immunity and immunoregulation is essential to spare the host from both unrestricted viral replication as well as severe disease after infection.…”
Section: Discussionmentioning
confidence: 98%
“…The role of Tregs has been controversial for a long time, as it was related to counterbalance Th1 response ( 79 ). This concept was progressively refined, placing Tregs in a more neutral role, without increasing the bacillary load in lesions at all ( 80 ), or even a protective one ( 81 , 82 ). The fact is that the models that were used did not develop human-like lesions, and therefore, the role of pathology and exudative progression was not explored.…”
Section: The Quest For a New Vaccine Against Tbmentioning
confidence: 99%